Pengaruh Transformational Leadership terhadap Teacher Performance Pada Sekolah Kristen dengan School Climate Sebagai Variabel Mediasi - Irawan, Agathon Charis; Wijaya, Serli; Jaolis, Ferry (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2024)
Abstract: The purpose of this research is to examine the impact of Transformational Leadership and School Climate on Teacher Performance. The survey was conducted on teachers from five Christian high schools located in Surabaya and Sidoarjo. The sample was selected by convenience where as many as 103 teachers were willing to participate in the survey conducted. Using the SEM-PLS statistical technique to process the collected primary data, the results showed that transformational leadership had a direct, positive and significant effect on school climate but had no significant effect on teacher performance. Furthermore, school climate has a direct, positive and significant effect on teacher performance. What's interesting is that transformational leadership has a positive and significant effect on teacher performance when mediated by school climate. Thus, school climate is a perfect mediating variable in which transformational leadership applied by school leaders will have a significant effect on teacher performance only when the school climate is also considered positive.Keywords: transformational leadership, school climate, teacher performanceAbstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh Transformational Leadership dan School Climate terhadap Teacher Performance. Survei dilakukan kepada para guru dari lima SMA Kristen yang terletak di Surabaya dan Sidoarjo. Sampel dipilih secara convenience dimana sebanyak 103 guru yang sedia berpartisipasi dalam survei yang dilakukan. Menggunakan teknik statistik SEM-PLS untuk mengolah data primer yang terkumpul, hasil penelitian menunjukkan bahwa transformational leadership secara langsung, berpengaruh positif dan signifikan terhadap school climate namun tidak berpengaruh signifikan terhadap teacher performance. Selanjutnya, school climate secara langsung, berpengaruh positif dan signifikan terhadap teacher performance. Yang menarik adalah transformational leadership berpengaruh positif dan signifikan terhadap teacher performance ketika dimediasi oleh school climate. Dengan demikian, school climate merupakan variabel mediasi sempurna dimana kepemimpinan transformational yang diterapkan oleh pimpinan sekolah akan signifikan pengaruhnya terhadap kinerja guru hanya ketika iklim sekolah dinilai juga ikut positif.Kata kunci: transformational leadership, school climate, teacher performance